2015
DOI: 10.1002/chir.22535
|View full text |Cite
|
Sign up to set email alerts
|

A Simple 13C NMR Method for the Discrimination of Complex Mixtures of Stereoisomers: All Eight Stereoisomers of α‐Tocopherol Resolved

Abstract: A simple one-dimensional (13)C NMR method is presented to discriminate between stereoisomers of organic compounds with more than one chiral center. By means of this method it is possible to discriminate between all eight stereoisomers of α-tocopherol. To achieve this the chiral solvating agent (S)-(+)-1-(9-anthryl)-2,2,2-trifluoroethanol and the compound of interest were dissolved in high concentrations in chloroform-d, and the nuclear magnetic resonance (NMR) spectrum was recorded at a low temperature. The in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 29 publications
2
7
0
Order By: Relevance
“…This strategy becomes more attractive mainly when the 1 H-NMR spectra demonstrate broad multiplets and small chemical shift differences between the stereoisomers. As a result, Lankhorst et al presented a simple 13 C-NMR methodology for the discrimination of a complex mixture of α-tocopherol stereoisomers [ 75 ]. The traditional methods employed to perform this discrimination, such as gas and liquid chromatography, require multiple steps to prepare the sample and obtain the ideal conditions.…”
Section: 13 C-nmr Chiral Recognitionmentioning
confidence: 99%
“…This strategy becomes more attractive mainly when the 1 H-NMR spectra demonstrate broad multiplets and small chemical shift differences between the stereoisomers. As a result, Lankhorst et al presented a simple 13 C-NMR methodology for the discrimination of a complex mixture of α-tocopherol stereoisomers [ 75 ]. The traditional methods employed to perform this discrimination, such as gas and liquid chromatography, require multiple steps to prepare the sample and obtain the ideal conditions.…”
Section: 13 C-nmr Chiral Recognitionmentioning
confidence: 99%
“…Very recently, we have shown that one important advantage of 1D 13 C NMR is the extremely high resolution that can be obtained, which led to the discrimination of all eight stereoisomers (four diastereomeric pairs of enantiomers) of the three-chiral-carbon containing α-tocopherol (Vitamin E). We could assign all eight stereoisomers, and 0.75% of a minor stereoisomer could be detected in a sample of pure RRR α-tocopherol in an NMR experiment of 30 min (256 scans) [ 13 ]. The use of multinuclear NMR for enantiodiscrimination has been reviewed recently [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…We previously demonstrated that all eight stereoisomers of α-tocopherol, which contains three chiral centers, could be identified by means of one-dimensional (1D) 13 C NMR. [1] In the present contribution, we show that the superior resolution of 1D 13 C NMR even allows for the discrimination between all 16 stereoisomers of a compound with four chiral centers: 4-hydroxy-α-tocopherol (1; Figure 1).…”
Section: Introductionmentioning
confidence: 66%
“…For general information on experimental procedures, see ref. [1] Purities given were measured by quantitative 1 H NMR, unless otherwise noted.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation